Reprodução experimental e caracterização clínicopatológica da mamilite pelo herpesvírus bovino tipo 2 (BoHV-2) em ovinos. - Almeida, Sabrina Ribeiro de (2006)
The bovine mammillits caused by bovine herpesvirus type 2 (BoHV-2) is an important disease of dairy cattle yet very little is known about its pathogenesis. This study aimed at reproducting and characterizing the clinical-pathological aspects of bovine herpesvirus mammillits in experimentally infected sheep. In the first experiment, ten lambs were inoculated in the nasal mucosa and the virological, clinical and serological aspects of acute infection were monitorated. Virus sheeding was detected in nasal secretions of 7 lambs between days 2 and 8 post inoculation (pi) and lasted from one to three days. A serous nasal discharge, changing to mucous and mucopurulent, was observed in all animals between days 2 and 5 pi. Seven lambs developed vesicles, pustules and erosions in the nasal mucosa between days 4 and 8 pi. All inoculated animals seroconverted to BoHV-2. Dexamethasone administration at day 40 pi was not followed by virus shedding, clinical recrudescence or seroconversion. In the second experiment, eight milking ewes were inoculated in the skin of the teats and udder, and monitorated thereafter regarding to viral replication, clinical signs and histological changes. Infectious virus was isolated from lesion swabs of one ewe on days 7 and 8 pi. Five animals developed lesions in inoculation sites between days 4 and 6 pi. The clinical-pathological aspects of the lesions were similar to those of natural infections and were characterizated by erythema, edema, papules, vesicles, exsudation and scabs. By histological examination, the lesions displayed cellular edema and linfoplasmocitic multifocal infiltrate surrounding blood vessels in the dermis. Moreover, eosinophilic intranuclear inclusion bodies were observed in inflamatory cells and syncitia. Virus particles resembling herpesvirus were observed by eletronic transmission microscopy. These results indicate that sheep are susceptible to BoHV-2 infection, and can develop clinical signs similar to those observed in cattle in natural outbreaks of herpes mammillitis. Thus, this animal species may be used as a model to study pathogenesis, vaccine development and antiviral drugs.